A New Twist on Old Questions: A Life Span Approach to the Trait Concept. Issue 1 (29th March 2017) - Hampson, Sarah E.; Edmonds, Grant W.
Abstract: Objective: We examine three cardinal concerns in personality psychology from a life span perspective: trait structure, trait stability, and trait mechanisms that account for the predictive utility of traits. We draw on previously published and new findings from the Hawaii Longitudinal Study of Personality and Health, as well as work by others. Method: The Hawaii study provides a unique opportunity to relate a comprehensive assessment of participants' childhood personality traits (over 2, 000 children, mean age 10 years) to their adult personality traits and other self‐report outcomes in their 40s, 50s, and 60s, and their clinically assessed health at mean age 51. Results: Our analyses have demonstrated that the Big Five can be used to describe childhood personality in this cohort. The stability of the Big Five from childhood teacher assessments to adult self‐ or observer reports is modest and varies from Big Five trait to trait. Personality mechanisms of life span health behavior and life span trauma experience explain some of the influence of childhood Conscientiousness on adult health outcomes. Conclusions: A life span approach highlights the dynamic nature of traits and their long‐term predictive utility, and it offers numerous directions for future research.